The impact of workplace injustice towards employee wellbeing / Anis Farhana Mohammad Kamal - Kamal, Anis Farhana Mohammad (2019)
The existence of unpleasant colleagues; those who enjoy making other people’s life miserable by discriminating and abusing their power, or hostile colleagues who are expert at oppressing others at the workplace are frequent challenges nowadays. Previous research on hostile work environment has narrowed its boundaries by portraying heavily from psychological and social-psychological viewpoints. The literature has documented a lot of adverse mental health consequences of hostile work environment. The purpose of this study is to discuss the nature of hostile work environment and its damaging effects on individuals and the organization, and the approaches to handle such undesirable environment. In addition, this study aims to examine the progressions by which the victims who experience the ongoing emotional trauma in response to the hostile work environment. The design of this study was in dept semi-structured interview with the critical perspectives. This study first identifies the phenomenon of hostile environment such as incivility and injustice at the workplace and then interviews the victims of their experiences